Nutraceuticals in Diabetes Management - Rehan Haider; Asghar Mehdi; Anjum Zehra; Geetha Kumari Das; Zameer Ahmed (International Journal of Integrative Sciences, 2024)
Nutraceuticals, a suitcase of "food" and "pharmaceuticals," represent a blooming field in the administration of diabetes. With the all-encompassing predominance of diabetes reaching its disquieting dimensions, there is a growing need for complete approaches to complement normal analyses. Nutraceuticals, including bioactive compounds derived from snack beginnings, have attracted attention for their potential to prevent and treat diabetes.Polyphenols in various products, legumes, and teas have shown antagonistic diabetic properties by modulating sweet substance absorption and insulin sensitivity. curcumin fatty Curcumin, a bioactive compound in turmeric, demonstrates antagonistic-instigative and antioxidant properties, providing improved glycemic control. Omega-3 fatty acids, which are widespread in extricate oils, exhibit insulin-sensitizing properties and can diminish diabetic complexities. Additionally, dietary texture—a plethora of whole grains and legumes—aids the level of glucose in blood management and pressure administration. Nutraceuticals offer further glycemic control; however, they still address the associated problems of diabetes. Antioxidant-rich vitamins, such as C and E, protect against oxidative stress, which is involved in diabetic complications. insulin. Furthermore, certain minerals, to a certain degree chromium and magnesium, play crucial roles in insulin, indicating oxygen absorption